If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(25*x)/45 = -67 // + 67
(25*x)/45+67 = 0
5/9*x+67 = 0 // - 67
5/9*x = -67 // : 5/9
x = -67/5/9
x = -603/5
x = -603/5
| 2(5x-6)-3(1-x)=4-6(x+2) | | 5/7÷1/3 | | 12-3(4w-1)=7w-3(7+w) | | 2x+7-3x=6x-1 | | 6-2x-1=4x+6-6x-3 | | -(5b-1)=5b-(b-4) | | 7y^2-68y-20=0 | | -5-3(1-8p)=18-2p | | 2y-3x(x-8)=0 | | -103+2x=44-5x | | 232=-8(3x-5) | | 9x-9=18+6x | | 3+4y=15 | | 7-3r=r-(r+1) | | -2(3x-7)=36 | | 16+4x+3=-2x-(-6x)+12-(-7) | | 5x-100=-2x+40 | | 7x-4=-11x+6 | | 25x/45=-67 | | 1+7x=-5x-23 | | -4(1+k)=-3-3k | | (3y^2-8y+1)-(2y^2-8y+8)= | | -37-x=35-9x | | -3r-12=4-r | | x-7/6=2 | | X*4=100 | | 10n+5-8n-3=12 | | 2(m+3)= | | 9-5/8x=10 | | 12-15x(-5)= | | x^2+22x=-84+10x | | 7n+29=8 |